Ascophyllum nodosum Extract (SealicitTM) Boosts Soybean Yield Through Reduction of Pod Shattering-Related Seed Loss and Enhanced Seed Production - Łangowski, Łukasz; Goñi, Oscar; Marques, Fabio Serafim; Hamawaki, Osvaldo Toshiyuki; da Silva, Carolina Oliveira; Nogueira, Ana Paula Oliveira; Teixeira, Morgana Aparecida Justino; Glasenapp, Jacqueline Siqueira; Pereira, Marcio; O’Connell, Shane (Frontiers in Plant Science, 2021)
Soybean is one of the most valuable commercial crops due to its high protein, carbohydrate and oil content. The land area cultivated with soybean in subtropical regions, such as Brazil, is continuously expanding, in some instances at the expense of carbon storing natural habitats. Strategies to decrease yield/seed losses and increase production efficiency are urgently required to meet global demand for soybean in a sustainable manner. Here, we evaluated the effectiveness of an Ascophyllum nodosum extract (ANE), Sealicit™, in increasing yields of different soybean varieties, in two geographical regions (Canada and Brazil). In addition we investigated the potential of Sealicit™ to reduce pod shattering at the trials in Brazil. Three different concentrations of Sealicit™ were applied to pod shatter susceptible (SS) UFUS 6901 and resistant (SR) UFUS 7415 varieties to assess their impact on pod firmness. SS variety demonstrated a significant decrease in pod shattering, which coincided with deregulation of GmPDH1.1 and GmSHAT1-5 expression, genes that determine pod dehiscence, and higher seed weight per pod. Sealicit™ application to the SR variety did not significantly alter its inherent pod shatter resistance, but provided higher increases in seed yield at harvest. This yield increase was probably linked to other yield components stimulated by the biostimulant. This work demonstrates that, Sealicit™, which has previously been shown to improve pod firmness in Arabidopsis and selected commercial oilseed rape varieties through IND gene down-regulation, also has the potential to improve pod resistance and seed productivity in soybean, a member of the legume family sharing a similar strategy for seed dispersal.